(untitled) (Praxis Educativa, 2015)
The article aims to analyze the social representations of teachers about the processes of educational inclusion in secondary education for youth and adults. This approach is built on the basis of the inclusion of sectors that were excluded from the possibility of exercising the right to education. The ways in which teachers give meaning to inclusion is what we want to know, through the conceptual framework provided by the theory of social representations. The methodology combined qualitative and quantitative data collection strategies. The findings lead to affirm that social representations of teachers are complex and are traversed by contradictory conceptions. There is confidence in the possibilities of transforming and improving life opportunities offered by education, while underlying characteristics of a school closer to reproductivism positioning notions and meritocratic perspective.